The updated retrospective questionnaire study of sporadic inclusion body myositis in Japan - Suzuki, Naoki (Orphanet J Rare Dis, 2019)
BACKGROUND: Sporadic inclusion body myositis (sIBM) is the most prevalent muscle disease in elderly people, affecting the daily activities. sIBM is progressive with unknown cause and without effective treatment. In 2015, sIBM was classified as an intractable disease by the Japanese government, and the treatment cost was partly covered by the government. This study aimed to examine the changes in the number of patients with sIBM over the last 10 years and to elucidate the cross-sectional profile of Japanese patients with sIBM. METHODS: The number of sIBM patients was estimated through a reply-paid postcard questionnaire for attending physicians. Only patients diagnosed as “definite” or “probable” sIBM by clinical and biopsy sIBM criteria were included in this study (Lancet Neurol 6:620-631, 2007, Neuromuscul Disord 23:1044-1055, 2013). Additionally, a registered self-administered questionnaire was also sent to 106 patients who agreed to reply via their attending physician, between November 2016 and March 2017. RESULTS: The number of patients diagnosed with sIBM for each 5-year period was 286 and 384 in 2011 and 2016, respectively. Inability to stand-up, cane-dependent gait, inability to open a plastic bottle, choking on food ingestion, and being wheelchair-bound should be included as sIBM milestones. Eight patients were positive for anti-hepatitis C virus antibody; three of them were administered interferon before sIBM onset. Steroids were administered to 33 patients (31.1%) and intravenous immunoglobulin to 46 patients (43.4%). From 2016 to 2017, total of 70 patients applied for the designated incurable disease medical expenses subsidy program. Although the treatment cost was partly covered by the government, many patients expressed psychological/mental and financial anxieties. CONCLUSIONS: We determined the cross-sectional profile of Japanese patients with sIBM. Continuous support and prospective surveys are warranted.